If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6t + -8 = -7t Reorder the terms: -8 + -6t = -7t Solving -8 + -6t = -7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '7t' to each side of the equation. -8 + -6t + 7t = -7t + 7t Combine like terms: -6t + 7t = 1t -8 + 1t = -7t + 7t Combine like terms: -7t + 7t = 0 -8 + 1t = 0 Add '8' to each side of the equation. -8 + 8 + 1t = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 1t = 0 + 8 1t = 0 + 8 Combine like terms: 0 + 8 = 8 1t = 8 Divide each side by '1'. t = 8 Simplifying t = 8
| f(x)=3x^3-x^2+5x | | -8g=-9g-2 | | 3p-3=2 | | N-6=2n-16 | | X-.3x=114 | | -9(0)-2y=-20 | | 1.75y^2+2y=0 | | 7n+2=8 | | 22222x+69x=4 | | (x+y-z)(x+y+z)= | | 5y+3=y+1 | | An=(2n^2) | | 5x^3-15x^2+4x-12=0 | | x+(x-2)+2x=82 | | 43+26k=927 | | X^2-12-27=0 | | 8a+5=10 | | x-4=-5x-28 | | 740=-20(b+794) | | 5.9+x=0.8 | | 4y-3=2y+21 | | 49-2x+8= | | -5(0.1x+0.5)-0.8=-0.3 | | -4g=-36 | | n-15=-21 | | 3(2b-4)+14=26 | | 42=12+5(x-1) | | 192=72x^2+24X | | 6(x+3)-75=5(x-10) | | 5-5x=-8x+14 | | (12-15)3= | | 192=72x^2+24 |